2012
DOI: 10.2136/sh12-02-0006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Salinity and Sodium Levels on Soils before Drain Tile Installation: A Case Study

Abstract: Soil salinity has emerged as one of the most serious and widespread consequences of the climatic wet period affecting the northern region of the American Midwest since 1993. Groundwater levels have increased, causing not only millions of hectares of prevented planting in the Dakotas, but also much higher levels of soil salinity on otherwise productive soils. A persistent comment from producers throughout eastern North Dakota during the wet cycle was that salinity had emerged in areas where it was never a probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The results can also be applied to field soils since SAR increases with depth in many North Dakota soils (McClelland et al, 1959). The reduction of EC due to salt loss through tile drainage likely contributes to swelling in sodic zones and may help to explain the phenomenon that the drainage performance in some sodium-affected soils decreases after several growing seasons (Cihacek et al, 2012;Hopkins et al, 2012). Tile drainage is also being used to remediate saline and saline-sodic soils, for example in China (Wang et al, 2007), where the Chinese government has implemented a 121.4 million ha "red line" agricultural land quota which will likely bring marginal lands such as these into production.…”
Section: Implications For Subsurface Drainagementioning
confidence: 99%
“…The results can also be applied to field soils since SAR increases with depth in many North Dakota soils (McClelland et al, 1959). The reduction of EC due to salt loss through tile drainage likely contributes to swelling in sodic zones and may help to explain the phenomenon that the drainage performance in some sodium-affected soils decreases after several growing seasons (Cihacek et al, 2012;Hopkins et al, 2012). Tile drainage is also being used to remediate saline and saline-sodic soils, for example in China (Wang et al, 2007), where the Chinese government has implemented a 121.4 million ha "red line" agricultural land quota which will likely bring marginal lands such as these into production.…”
Section: Implications For Subsurface Drainagementioning
confidence: 99%
“…In the U.S. northern Great Plains (NGP) (North Dakota, South Dakota, Minnesota, Wyoming, Nebraska, and Montana), over 10.6 million ha of arable land have salinity and/or sodicity problems (Hopkins et al., 2012; Millar, 2003; Seelig, 2000), which can result in large yield and economic losses (Hadrich, 2012). The salinity/sodicity problem is driven by natural processes and results from sodium and other salts being transported from ancient seabeds to the soil surface.…”
Section: Introductionmentioning
confidence: 99%
“…As Hopkins et al (2012) suggested, saturated soil contributed to higher soil salinity, which prevented planting in the Dakotas.…”
Section: Forest Soil Characteristicsmentioning
confidence: 99%